Adaptive Immune Deficiency Impairs Neural Activity After Training and Retrieval - Li, Huiping; Fu, Zhongxiao; Hu, Meixin; Xu, Xiu (Frontiers in Neuroscience, 2021)
Neuroimmune interactions have been studied for decades. Several neurodevelopmental disorders have been associated with immune dysfunction. However, the effects of immune system on neuronal function remain unknown. Herein, based on c-Fos protein expression, we characterized the brain areas that are activated after contextual fear conditioning (CFC) training or retrieval in severe combined immune deficiency (SCID) and wild-type mice. Further, we analyzed the interregional correlations of c-Fos activity that are affected by deficiency in adaptive immunity. Results showed significantly lower c-Fos density in learning and memory-associated brain regions of SCID mice after memory retrieval, but not during the CFC training. Moreover, SCID mice exhibited remarkably discordant inter-regional neuronal activities of learning neuron circuits after CFC training, which could be the cause of inefficient activation of the memory circuit after retrieval. These results provide a new perspective on how adaptive immunity affects neuronal function. Adaptive immune deficiency impairs the coordination of neural activity after training and retrieval which might be a potential therapeutic target for neurodevelopmental disorders.